Evaluation of Aircraft Emissions at Bucharest Henri Coanda Airport - Mirea, Radu; Cican, Grigore; Cretu, Mihaiella (Engineering, Technology & Applied Science Research, 2023)
This study presents the influence of aircraft movements on air quality by highlighting the contribution of landings and/or takeoffs at Henri Coanda Airport, Bucharest. An experimental campaign was carried out using a mobile laboratory equipped with reference instruments for the main air pollutants (NO-, NO2, NOx, SO2, CO, and O3) and a meteorological station to measure wind speed and direction, air temperature, pressure, and relative humidity at a height of 10 m above the ground. The mobile testing laboratory was located inside the airport near the passenger embarking area, and measurements were carried out for 7 days. Air sampling was carried out at a height of 3.5 m above the ground. Pollutant levels were continuously measured throughout the measurement period, with high-precision equipment and a 10-second interval. The results obtained showed an increase in pollutant concentrations during takeoffs and/or landings, providing an initial assessment of gaseous pollutant levels and hourly distribution. Airport authorities can use this assessment to balance aircraft and passenger movements to minimize human exposure to gaseous pollutants. Furthermore, this study used the Pearson correlation between each pollutant and meteorological parameters to establish the best conditions for passengers to be present on the airport premises. The results showed that wind speed and direction directly influence the distribution of gaseous pollutants, especially during landings and takeoffs.